Escaping Social Pressure: Fixed-Term Contracts in Multi-Establishment Firms - Andrea Bassanini; Eve Caroli; Francois Fontaine; Antoine Rebérioux (Institute of Labor Economics (IZA), 2021)
We develop a simple theoretical model showing that, by adding to the adjustment costs associated with permanent contracts, local social pressure against dismissals creates an incentive for CEOs to rely on fixed-term contracts, in an attempt to escape social pressure. Using linked employer-employee data, we show that establishments located closer to headquarters have higher shares of fixed-term contracts in hiring than those located further away whenever firms' headquarters are located in self-centered communities and the CEO not only works but also lives there. We show that these findings can only be explained by local social pressure.
Keywords: J23; J41; M14; M55; R12; 330; social pressure; employment contracts; adjustment costs; CEO reputation